Television projects about culture through the prism of national mentality: the experience of Kazakhstan, Tajikistan, Kyrgyzstan - Nurash А.А.; Oshanova О.Ж.; Rozhkov А.В. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The study of art journalism in Central Asia is becoming increasingly relevant in the context of globalization and the strengthening of regional identity, as it helps to understand how local media practices interact with global trends. The purpose of the scientific work is to identify the phenomenon of modern art journalism, to identify effective tools of foreign media that can be introduced into the practice of domestic media. The article highlights the specifics of art-oriented media. The forms of interaction between journalism and culture are considered. The examples clearly explain the featuresand directions of art programs. To study the evolution of art journalism in the region, a historical method was used, while content analysis helped to systematically evaluate modern media content. The research has practical value for the development of cultural dialogue, the maintenance of national identity and contributes to the deepening of cooperation in the region. The scientific significance lies in the fact that the results of the research part can be used in the study of art journalism in social networks and its influencing function on the preservation and transmission of cultural heritage.